2018
DOI: 10.1002/acr.23571
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Psoriatic Arthritis According to Different Definitions of Disease Activity: Comparing Minimal Disease Activity and the Disease Activity Index for Psoriatic Arthritis

Abstract: Objective Treat‐to‐target strategies have improved outcomes in rheumatic diseases. In psoriatic arthritis (PsA), the proposed targets are the multidimensional target minimal disease activity (MDA) and the articular target Disease Activity index for PsA (DAPSA). The aim of this study was to compare the disease burden of PsA in patients with low disease activity according to the 2 definitions, MDA and DAPSA low disease activity (DAPSA‐LDA), 1 year after diagnosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 32 publications
7
17
0
Order By: Relevance
“…In the present study, we confirmed that the frequency of REM and LDA was very variable according to the definition used, and in particular REM and LDA were more difficult to reach using VLDA/MDA than DAPSA-based cut-offs, as has been previously reported 14–16. This may be because of the inclusion of diverse domains of PsA (and in particular skin involvement), or because of low cut-offs for each measure.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the present study, we confirmed that the frequency of REM and LDA was very variable according to the definition used, and in particular REM and LDA were more difficult to reach using VLDA/MDA than DAPSA-based cut-offs, as has been previously reported 14–16. This may be because of the inclusion of diverse domains of PsA (and in particular skin involvement), or because of low cut-offs for each measure.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, it is generalisable due to the international large-scale recruitment strategy of consecutive patients with PsA. Furthermore, frequencies of REM/LDA were similar to other studies, which supports the validity of the present findings 14–16. Another difficulty was to choose among many possible definitions of REM/LDA since no consensus exists.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We used data collected in the Dutch southwest Early Psoriatic Arthritis cohoRt (DEPAR) study, of which details are described elsewhere. 10 In short, DEPAR collects data to investigate the daily clinical practice of patients with PsA. Patients with a new diagnosis of PsA are eligible to participate if they did not yet receive treatment with disease-modifying antirheumatic drugs (DMARDs) for PsA before the first study visit.…”
Section: Methodsmentioning
confidence: 99%